Penguatan Nilai-Nilai Keislaman Melalui Penyelenggaraan Pekan Anak Sholeh pada Kuliah Kerja Nyata di Desa Bagagap - Anisah, Nor; Nuradiyanti, Irma; Wulandari, Erwila; Ramadani, Hardianor; Waang, Kris Andrianus Dominson; Sutanto, Agung; Sazali, Akhmad; Adawiyah, Rabiatul; Rahmah, Yulia; Noor, Muhammad Rajib (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2024)
Kuliah Kerja Nyata (KKN) aims to provide tangible contributions to community development, one of which is through the reinforcement of Islamic values. The implementation of the Pekan Anak Sholeh (Righteous Child Week) in Bagagap Village is an effort to strengthen Islamic values in children. This activity includes various competitions such as the call to prayer (azan) competition, tartil (Quran recitation) for boys and girls, and Islamic calligraphy coloring. The method used begins with preparation and planning, socialization, technical training, implementation and evaluation, involving village children as the main participants and the local community as event supporters. The results of the activity show increased enthusiasm and participation of children in understanding and practicing Islamic values, as well as boosting their self-confidence. The azan and tartil competitions enhance the children's abilities and courage in performing religious practices, while the calligraphy coloring competition fosters their love for Islamic art. Additionally, this activity strengthens social bonds between children and the community and provides a deeper understanding of the importance of practicing Islamic teachings in daily life. Therefore, the Pekan Anak Sholeh in Bagagap Village has proven effective in reinforcing Islamic values in children and can serve as a model for similar activities in Bagagap Village.